Pemanfaatan Cerita Rakyat Sebagai Penanaman Etika untuk Membentuk Pendidikan Karakter Siswa Kelas IV SD - Fadhilah, Syaufie; Hermansah, Bambang; Ayurachmawati, Puji (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this study was to describe the use of folklore as an inculcation of ethics to formcharacter education for grade IV A SD Negeri Karang Agung. The problem in this research is how to use folklore as an inculcation of ethics to shape character education in Indonesian class IVlearning at SDN Karang Agung. The research method used is descriptive qualitative method. Data collection techniques used are interview, observation and documentation techniques. The data analysis technique used is data reduction, data presentation and conclusion drawing. The research subjects in this study were grade IVA students at SD Negeri Karang Agung with a total of 20 students. The results in this study were that after the implementation of the ngujang monkeyfolklore, the overall percentage was 88.33% of students practicing the values of religiouscharacter, discipline and responsibility. While for each character values, 95% of students practicereligious values, 85% of students practice discipline values and 85% of students practiceresponsibility values. This shows that folklore can be used as an alternative in inculcating ethics instudent character education. Based on these results, it can be concluded that folklore can be used as a means of instilling ethics in student character education.